KONFLIK RUMAH TANGGA DAN SOLUSINYA MENURUT HUKUM ISLAM DAN PERATURAN PERUNDANG-UNDANGAN - Hifni, Mohammad (LPPM Universitas Bina Bangsa, 2024)
Marriage is not only a union of two human partners, a man and a woman, but a sacred covenant in the name of Allah Almighty. that the bride and groom intend to build a household that is sakinah, peaceful, and filled with love and affection. A marriage is only declared valid if according to the law it has fulfilled its pillars and conditions. Basically, the marriage is carried out for an eternal time until the death of one of the husband and wife. This is exactly what the religion of Islam wants. However, in certain circumstances there are things that require the breakup of the marriage in the sense that if the marital relationship continues, then harm will occur. In this respect Islam justifies the breakup of marriage as the last step of the effort to continue the household. The breakup of a marriage in such a way is a good way out